Transcranial magnetic stimulation measures of corticospinal excitability in Black and Hispanic/Latino people with painful peripheral neuropathy - Wong, Marlon L.; McTeague, Lisa M.; Gonzalez, Gabriel; Gonzalez, Juan P.; Bolanos, Jessica L.; Hosein, Peter J.; Cabral, Danylo F.; Fried, Peter J. (Frontiers in Human Neuroscience, 2025)
IntroductionThis study aims to provide preliminary descriptive data on transcranial magnetic stimulation (TMS) measures obtained in Black and Hispanic/Latino individuals with chronic painful peripheral neuropathy (PN), including those with chemotherapy-induced peripheral neuropathy (CIPN) and diabetic neuropathy (DN). Both CIPN and DN share similar neuropathic symptoms and underlying physiological mechanisms, in particular altered central nervous system processing. TMS is a non-invasive technique that can assess corticospinal excitability and the function of GABAergic and glutamatergic pathways, potentially serving as a diagnostic or prognostic tool for PN.MethodsThis study utilized data from a pilot randomized sham-controlled trial that tested the impact of patient education videos on the effect of transcutaneous auricular vagus nerve stimulation (taVNS) in Black and Hispanic/Latino individuals living with PN. TMS measures, including resting motor threshold (RMT), MEP amplitude following unconditioned single-pulse TMS (spTMS) and paired-pulse TMS measures of short interval intracortical inhibition (SICI), and intracortical facilitation (ICF), were assessed twice on separate visits. Test-retest reliability was evaluated, and changes in TMS measures following transcutaneous auricular vagus nerve stimulation were computed.ResultsPre-intervention TMS measures showed smaller-than-medium sized differences between CIPN and DN groups. The study found good test-retest reliability for TMS measures, with ICC values between 0.69 and 0.95 for all TMS measures of interest.DiscussionOverall, TMS measures demonstrated good reliability in this sample of Black and Hispanic/Latino individuals with PN, and these findings provide valuable preliminary data for future studies aimed at establishing the psychometric properties and diagnostic utility of TMS measures in PN.